2015
DOI: 10.1016/j.joa.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

Pace mapping in the atrium using bipolar electrograms from widely spaced electrodes

Abstract: Use of three bipolar electrograms recorded from a set of widely spaced electrodes in the right atrium improves the resolution of pace mapping compared to that using P waves from surface electrocardiograms alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Selvaraj et al reported the accuracy of manual P wave PM. 17 They indicated that paced match score at the same paced site was 11.5±0.6 out of 12 for the 12-lead ECG evaluated by blinded observer. This result supports P wave pacing methodology.…”
Section: P Wave and Intracardiac Activation Sequence During Pmmentioning
confidence: 99%
See 1 more Smart Citation
“…Selvaraj et al reported the accuracy of manual P wave PM. 17 They indicated that paced match score at the same paced site was 11.5±0.6 out of 12 for the 12-lead ECG evaluated by blinded observer. This result supports P wave pacing methodology.…”
Section: P Wave and Intracardiac Activation Sequence During Pmmentioning
confidence: 99%
“…In another study, the spatial resolution of PM in atrium using unipolar pacing was 9.9 mm. 17 Although significant changes in P wave amplitude and duration can be detected, the magnitudes are small and often visually indiscernible. However, FAT usually originates from particular complex structures (eg, crista terminalis, PVs, CS ostium, and around the annulus).…”
Section: P Wave and Intracardiac Activation Sequence During Pmmentioning
confidence: 99%